Cover Image:. Issue 7 (26th October 2019) - Kasahara, Mami; Kobayashi, Chiaki; Yamanaka, Akira; Kitazawa, Chisato
Abstract : ON THE COVER : The cover image is based on the Research Article Regeneration of the cell mass in larvae of temnopleurid sea urchins by Mami Kasahara et al., https://doi.org/10.1002/jez.b.22899